PROTECTION OF PROCEDURAL RIGHTS OF PARTICIPANTS IN CRIMINAL PROCEEDINGS AT THE STAGE OF PRE-TRIAL INVESTIGATION: THEORETICAL-LEGAL AND CRIMINALIST ASPECTS (Bulletin of criminological association of Ukraine, 2025)
The article conducts a comprehensive study of procedural guarantees as a key tool for ensuring the rights and freedoms of persons participating in criminal proceedings. The main attention is focused on clarifying the content and legal nature of the concept of "procedural guarantees". The problematic aspects of the implementation of the rights of participants in the pre-trial investigation are revealed, taking into account modern law enforcement practice. An analysis of existing scientific approaches to the interpretation of criminal procedural guarantees is carried out, and their essential features are highlighted. Special attention is paid to the role of forensics in ensuring the implementation of procedural rights at the pre-trial stage. In particular, emphasis is placed on the importance of forensic tactics in conducting investigative (search) actions, which require strict observance of the rights of suspects, victims, witnesses and other participants in the proceedings. Forensic recommendations on documenting investigative actions, applying specialized knowledge, and preventing violations of procedural form are considered. It is substantiated that the introduction of forensic tools and methods allows not only to effectively solve crimes, but also to guarantee compliance with legal standards in the criminal process, in particular - within the framework of ensuring procedural guarantees.
Keywords: procedural guarantees; criminal process; pre-trial investigation; participants in criminal proceedings; forensics; procedural form; legal status; investigative action; evidence